Telemedicine to deliver diabetes care in low-and middle-income countries - Correia, Jorge César (2021)
Objective  To determine the effectiveness of telemedicine in the delivery of diabetes care in low- and middle-income countries. Methods  We searched seven databases up to July 2020 for randomized controlled trials investigating the effectiveness of telemedicine in the delivery of diabetes care in low- and middle-income countries. We extracted data on the study characteristics, primary end-points and effect sizes of outcomes. Using random effects analyses, we ran a series of meta-analyses for both biochemical outcomes and related patient properties. Findings  We included 31 interventions in our meta-analysis. We observed significant standardized mean differences of −0.38 for glycated haemoglobin (95% confidence interval, CI: −0.52 to −0.23; I2 = 86.70%), −0.20 for fasting blood sugar (95% CI: −0.32 to −0.08; I2 = 64.28%), 0.81 for adherence to treatment (95% CI: 0.19 to 1.42; I2 = 93.75%), 0.55 for diabetes knowledge (95% CI: −0.10 to 1.20; I2 = 92.65%) and 1.68 for self-efficacy (95% CI: 1.06 to 2.30; I2 = 97.15%). We observed no significant treatment effects for other outcomes, with standardized mean differences of −0.04 for body mass index (95% CI: −0.13 to 0.05; I2 = 35.94%), −0.06 for total cholesterol (95% CI: −0.16 to 0.04; I2 = 59.93%) and −0.02 for triglycerides (95% CI: −0.12 to 0.09; I2 = 0%). Interventions via telephone and short message service yielded the highest treatment effects compared with services based on telemetry and smartphone applications. Conclusion  Although we determined that telemedicine is effective in improving several diabetes-related outcomes, the certainty of evidence was very low due to substantial heterogeneity and risk of bias.  Objetivo Determinar la eficacia de la telemedicina en la prestación de servicios de atención sanitaria de la diabetes en los países con ingresos bajos y pocos medios. Métodos Se realizaron búsquedas en siete bases de datos hasta julio de 2020 para encontrar ensayos controlados aleatorios que investigaran la eficacia de la telemedicina en la prestación de servicios de atención de la diabetes en países con ingresos bajos y pocos medios. Se extrajeron datos sobre las características del estudio, las principales variables de evaluación  y  los  tamaños  del  efecto  de  los  resultados.  Utilizando  el  análisis de los efectos aleatorios, realizamos una serie de metaanálisis tanto  para  los  resultados  bioquímicos  como  para  las  propiedades  relacionadas con los pacientes. Resultados  Incluimos  31  intervenciones  en  nuestro  metaanálisis.  Se  observaron diferencias medias estandarizadas significativas de -0,38 para la hemoglobina glicosilada (intervalo de confianza del 95%, IC: -0,52 a -0,23; I2 = 86,70%), -0,20 para la glucemia en ayunas (IC del 95%: -0,32 a -0,08; I2 = 64,28%), 0,81 para el cumplimiento del tratamiento (IC del 95%: 0,19 a 1,42; I2 = 93,75%), 0,55 para el conocimiento de la diabetes (IC del 95%: 0,10 a 1,20; I2 = 92,65%) y 1,68 para la autoeficacia (IC del 95%: 1,06 a 2,30; I2 = 97,15%). No se observaron efectos significativos del tratamiento para otros resultados, con diferencias medias estandarizadas de  -0,04  para  el  índice  de  masa  corporal  (IC  del  95%:  -0,13  a  0,05;  I2 = 35,94%), -0,06 para el colesterol total (IC del 95%: -0,16 a 0,04; I2 = 59,93%) y -0,02 para los triglicéridos (IC del 95%: -0,12 a 0,09; I2 = 0%). Las intervenciones telefónicas y el servicio de mensajes cortos de texto produjeron los efectos de tratamiento más altos en comparación con los servicios basados en la telemetría y las aplicaciones de los teléfonos inteligentes. Conclusión Aunque se determinó que la telemedicina es eficaz para mejorar  varios  resultados  relacionados  con  la  diabetes,  la  certeza  de  las pruebas fue muy baja debido a la considerable heterogeneidad y el riesgo de sesgo.